The return of the long-run Phillips curve - Liam Graham; Dennis J. Snower (Centre for Economic Policy Research (CEPR), 2003)
This Paper integrates microfoundations of wage staggering into a simple dynamic general equilibrium model with rational expectations. In this context we show that a permanent increase in money growth leads to a permanent increase in the rate of inflation and a permanent reduction in the level of unemployment. In short, we derive a microfounded long-run downwardsloping Phillips curve.
Keywords: E20; E30; E40; E50; 330; Phillips-Kurve; Mikroökonomische Fundierung